No one was supposed to die at this wedding : a novel - Mack, Catherine (Mack, Catherine. Vacation mysteries, 2025)
"The second in a witty, USA Today bestselling series following author Eleanor Dash as she goes from wedding guest to murder mystery investigator at her best friend's wedding on Catalina Island. Attending your best friend's wedding should be a piece of (wedding) cake, but not for Eleanor Dash, bestselling author of the Vacation Mysteries series. Because murder seems to follow her every time she goes on vacation and is definitely her uninvited plus-one to the special occasion. Emma Wood, Eleanor's best friend since childhood, is starring in the movie adaptation of When in Rome, Eleanor's first novel. Emma is also marrying Fred Winters, a major movie star and Emma's co-star, who just happens to be playing Connor Smith, Eleanor's ex and leading man of the series. Filming wraps and they invite the whole cast and crew to their wedding at nearby Catalina Island. There may be a storm headed their way-because of course there is-but nothing will stop their nuptials . . . that is until Emma receives a note that says "Someone is going to die at the wedding." Eleanor is a professional at this point, and she'll do everything she can to uncover the murderer so true love can prevail . . . before it's too late for her and the rest of the storm-trapped wedding party"--